Effect of antidepressant treatment on cognitive impairments associated with depression: a randomised longitudinal study. (May 2016) - Shilyansky, Carrie; Williams, Leanne M; Gyurak, Anett; Harris, Anthony; Usherwood, Timothy; Etkin, Amit
Summary: Background: Antidepressant treatment failure is a common problem worldwide. In this study, we assess whether or not an important aspect of depression, cognitive impairment, is untreated by antidepressants by studying the effect of acute antidepressant treatment on a range of cognitive domains. Methods: In this randomised longitudinal study, which is part of the International Study to Predict Optimized Treatment in Depression (iSPOT-D) trial, we assessed the effects of acute antidepressant treatment in a large patient population, across clinical remission outcomes, on a range of cognitive domains: attention, response inhibition, executive function during visuospatial navigation, cognitive flexibility, verbal memory, working memory, decision speed, information processing speed, and psychomotor response speed. We enrolled patients from primary or specialty care clinics in a multicentre, international, open-label, randomised, prospective trial. Eligible patients (aged 18–65 years) were previously untreated or were willing to undergo a 1-week medication washout before the study start, and could not have had inadequate response to study medications in the past. We enrolled a large population of medication-free (ie, untreated) outpatients in a depressive episode and assessed them for cognitive function at enrolment (pre-treatment), and again after 8 weeks of treatment with one of three antidepressant drugs (escitalopram, sertraline, or venlafaxine extended-release). Patients were randomly assigned (1:1:1) to one of the three antidepressants using a blocked randomisation procedure (block size of 12). As a comparison group, we also simultaneously enrolled matched healthy participants. Healthy participants received no medication or intervention, but were assessed for change in cognitive and clinical measures during the same interval and testing protocol. Therefore, this group acts as a test–retest control for the primary outcome measure examined in this study, change in cognitive measures over 8 weeks of treatment in depressed patients. This study is registered withClinicalTrials.gov, numberNCT00693849 . Findings: Between Dec 8, 2008, and Sept 30, 2011, we enrolled 1008 eligible people into the study. Impairment in five domains—attention, response inhibition, verbal memory, decision speed, and information processing—showed no relative improvement with acute treatment (controlling for time or repeated testing), irrespective of antidepressant treatment group, even in patients whose depression remitted acutely according to clinical measures. Broader cognitive impairment was associated with greater illness chronicity (earlier illness onset) but not with symptom severity or previous antidepressant failures. Interpretation: Depression is associated with impairments in higher-order cognitive functions and information processing, which persist independently of clinical symptom change with treatment. We recorded no difference between the three antidepressants tested, with none showing efficacy for these impairments. Although the 8-week treatment period limits interpretation to acute treatment effects, it does highlight cognitive impairment as an untargeted contributor to incomplete treatment success. Funding: Brain Resource Company Operations Pty Ltd and NIH.